Biodegradation of phenol by a Malaysian isolate Rhodococcus sp. NAM 81 - Mohammad Nawawi, Norazah (2016)
Phenol is a major threat to the environment due its toxicity effect and extensive use in various industries. Phenol can harm human and other organisms at a low dose. Phenols and phenolic compounds are organic pollutants generated from various industrial activities. Biodegradation is a technology that is currently applied for decontaminating pollutants including phenols. Biodegradation of phenols using microorganism is an eco-friendly and cost-effective approach. Bacteria are widely used in bioremediation processing. Thus, the isolation and selection of good microorganism with tolerance towards other toxicants is important to improve the performance of bioremediation.This study evaluates the potential of a local Rhodococcus bacteria to decompose phenol, an oxygenated hydrocarbon, one of the harmful pollutants, because of its toxic and carcinogenic effects. Ten strains of Rhodococcus spp. isolated from Peninsular Malaysia survived and grew in a medium that was supplemented with 0.5 gL-1 of phenol. The 1500 bp phenol hydroxylase gene was amplified from the eight strains as a confirmation of phenol-degradation pathway and for future molecular marker for the presence of phenol-degrading bacteria. One strain, Rhodococcus sp. NAM 81 was selected as the most potent strains with the ability to decompose 0.6 gL-1 phenols within 24 hours. The phenol biodegradation ability of Rhodococcus sp. NAM 81 was greatly affected by the presence of trace element in the medium. The parameters tha supported the degradation and growth of Rhodococcus sp. NAM 81 were optimized initially by one-factor at a time approach. The strain exhibited highest cell growth and phenol degradation at the optimal incubation conditions of 30 °C and pH 7.5.Ammonium sulphate 0.4 gL-1, glycine 0.3 gL-1, and 0.1 gL-1 NaCl were needed to enhance cell growth. Apart from phenol, the strain was able to utilizes 1 mg L-1 of 2,4-dinitrophenol, toluene,naphthalene, diesel, acetonitrile, glycerol and waste cooking oil as the sources of carbon for growth, but the phenol degradation ability was inhibited by 1 mg L-1 of Ag+, Cu2+, Cr2+, Cd2+, Zn2+ and Hg2+. Statistical approach by fractional factorial design (FFD) and response surface method (RSM) improved the biodegradation of phenol with pH, phenol and NaCl concentrations were found to be important parameters. The results showed good verification between theoretical and experimental data. RSM method improves the process by 1.2 fold for phenol degradation and 1.3 fold for cell growth. Investigation on the application of immobilized cells in phenol biodegradation started with an evaluation of suitable matrices such as gellan gum, calcium alginate, agarose, agar-agar and polyacrylamide for phenol degradation using an immobilization approach. Gellan gum was found to be the most effective and suitable matrix for high phenol degradation compared to other matrices studied. Maximum phenol degradation was achieved at the gellan gum concentration of 0.75% (w/v), bead size of 3 mm diameter and bead number of 300 per 100 mL medium. Both free and immobilized bacteria exhibited similar rates of phenol degradation at the phenol concentration of 100 mgL-1, but at higher phenol concentrations, immobilized bacteria exhibited a higher degradation rate of phenol.The immobilized cells completely degrade phenol within 108, 216, and 240 h at 1100,1500 and 1900 mgL-1 phenol, respectively, whereas free cells took 240 h to completely degrade phenol at 1100 mgL-1. In overall, the rates of phenol degradation by both immobilized and free bacteria decreased gradually as the phenol concentrations were increased. It also proved that inhibition of heavy metal and respiratory inhibitors was prevented by gellan gum encapsulated cells. The immobilized cells showed no loss in phenol degrading activity after being used repeatedly for 50 repetitions of 18 h cycle and was stable after storing at 4 ºC for 28 days. Study on the best disruption methods for efficient enzyme, protein and genomic DNA isolation from Rhodococcus cells showed that grinding for 20 minutes under liquid nitrogen was the best approach.The ortho-cleavage pathway as applied by Rhodococcus sp. NAM 81 for phenol degradation was discovered by biochemical and polymerase chain reaction. The gene for phenol hydroxylase; the enzyme that catalyzes the conversion of phenol to catechol, has been cloned, expressed and purified from Rhodococcus sp. NAM 81.SDS-PAGE produced a single band with a molecular weight of ~ 60 kDa. The potential of resting cells of Rhodococcus sp. NAM 81 as an alternative to the use of free and immobilized cells for phenol biodegradation process in liquid waste was also tested. The results from this study showed that Rhodococcus sp. NAM 81 has an excellent potential that can be applied in bioremediation of phenol-containing wastes especially using immobilized cells.